2016
DOI: 10.1016/s1514-0326(16)30011-3
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Informality: A Comprehensive Panel Data Analysis

Abstract: In this paper we empirically explore the impact of the presence of informal economies on long-run economic growth. Using a novel panel dataset of 161 countries over the period from 1950 to 2010 we obtain an inverted-U relationship between informal sector size and growth of GDP per capita. That is, small and large sizes of the informal economy are associated with little growth and medium levels of the size of the informal economy are associated with higher levels of growth. We also observe that in high (low) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 18 publications
(16 reference statements)
4
37
0
2
Order By: Relevance
“…However, the economic situation was influential, since our analyses revealed that economic crises (CRISIS) have a negative impact on a country's economic growth, as expected (β = −3.429; p = 0.000). Finally, it is also worth mentioning that we considered controlling for the effects of the informal sector, due to its potential impact on economic growth, as shown in [80,81] which noted that the informal sector consists of all activities operating outside the official legal and fiscal system, with a resulting lack of reliable statistical information. In fact, this lack of data represented such a reduction in our sample size, which would have dropped from 1719 to 64 observations as well as in the number of countries (which would have dropped from 127 to 18), that its use as control variable is discouraged.…”
Section: Resultsmentioning
confidence: 99%
“…However, the economic situation was influential, since our analyses revealed that economic crises (CRISIS) have a negative impact on a country's economic growth, as expected (β = −3.429; p = 0.000). Finally, it is also worth mentioning that we considered controlling for the effects of the informal sector, due to its potential impact on economic growth, as shown in [80,81] which noted that the informal sector consists of all activities operating outside the official legal and fiscal system, with a resulting lack of reliable statistical information. In fact, this lack of data represented such a reduction in our sample size, which would have dropped from 1719 to 64 observations as well as in the number of countries (which would have dropped from 127 to 18), that its use as control variable is discouraged.…”
Section: Resultsmentioning
confidence: 99%
“…This paper focuses on the long-term determinants of the size of the shadow economy while Elgin and Birinci (2016) explores the nonlinear impact of the shadow economy on economic growth. The first difference of these two papers is the direction of the impact as Elgin and Birinci (2016) aims to identify one new factor of growth. Second, there is no direct inference between the two papers findings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, there is no direct inference between the two papers findings. Elgin and Birinci (2016) finds the inverted-U between the shadow economy and growth of GDP per capita. Given that growth of GDP per capita has no simple monotone relationship with the level of GDP per capita, it is hard to derive from their findings a relationship between the shadow economy and GDP per capita and thus to judge whether our paper is consistent with theirs or not.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Official GDP was 34% in 1999 but decreased to 31.2% in 2007, the decrease was mostly noticed in the unemployment rate. Elgin and Birinci (2015) analyzed the impact of the informal economies on economic growth of 161 countries from 1950-2010. The findings indicated that both small and large sizes of shadow economy had relationship with little growth in GDP per capita while the medium sizes of informal economy could be associated with higher levels of growth in GDP per capita.…”
Section: Empirical Reviewmentioning
confidence: 99%